Extreme Poleward Expanding Super Plasma Bubbles Over Asia‐Pacific Region Triggered by Tonga Volcano Eruption During the Recovery‐Phase of Geomagnetic Storm. Issue 15 (12th August 2022) - Rajesh, P. K.; Lin, C. C. H.; Lin, J. T.; Lin, C. Y.; Liu, J. Y.; Matsuo, T.; Huang, C. Y.; Chou, M. Y.; Yue, J.; Nishioka, M.; Jin, H.; Choi, J. M.; et al.
Abstract: The Tonga volcano eruption of 15 January 2022 unleashed a variety of atmospheric perturbations, coinciding with the recovery‐phase of a geomagnetic storm. The ensuing thermospheric variations created rare display of extreme poleward‐expanding conjugate plasma bubbles seen in the rate of total electron content index over 100–150°E, reaching ∼40°N geographic latitude. This is associated with fluctuations in FORMOSAT‐7/COSMIC‐2 (F7/C2) ion‐density measurements and spread‐F in ionograms. Preceding to this, an unusually strong pre‐reversal enhancement (PRE) occurred in the global ionospheric specification (GIS) electron density profiles derived from F7/C2 observations. The GIS also revealed a decrease of equatorial ionization anomaly (EIA) crest density due to the storm impact. Reduced E‐region conductivity by volcano‐induced waves and enhanced F‐region wind, further accelerated by reduced ion‐drag over the EIA, apparently intensified the PRE. Accompanied with the strong PRE, volcano‐induced seed perturbations triggered the super plasma bubble activity. Plain Language Summary: Rare things could happen when the centennial volcanic eruption occurred at the late stages of a magnetic storm driven by solar wind disturbances. The volcanic eruption drove atmosphere waves at the lower altitude in the ionosphere and the storm effect enhanced eastward wind at higher altitudes. The combined effect led to an unusual and substantial uplift of the post‐sunset ionosphere, known as pre‐reversal enhancement (PRE). The large layer uplift destabilized the bottomside ionosphere, leading to vigorous bubble‐like plasma irregularities, or plasma bubbles extending to middle latitudes, which are very rarely seen in January when the solar activity is low. This is the first time such super plasma bubbles are produced by the joint influence of geomagnetic and atmospheric forcings from above and below. Key Points: Tonga volcano eruption during a magnetic storm recovery‐phase triggered extreme equatorial plasma bubbles appearing even beyond Tokyo The volcano‐induced wave perturbations and unusually strong pre‐reversal enhancement (PRE) result in the rare development of plasma bubbles Reduced E‐region conductivity by the wave propagation and enhanced F‐region wind by negative storm at the equatorial anomaly intensify PRE